PENGARUH PENERAPAN PENDIDIKAN KARAKTER MODEL CHIPS DI SD XAVERIUS 1 UNTUK MENGEMBANGKAN KECERDASAN SPIRITUAL SISWA DARI PERSPEKTIF ORANG TUA - Sipayung, Erni; Widowati, Atri (Jurnal Pendidikan Tematik Dikdas, 2022)
This research is specifically conducted how the application of the CHIPS Character Education Learning Method in improving the spiritual attitudes and to find out the benefits of applying the CHIPS Character Education Learning Model in improving the spiritual attitudes of Grade 6B students at SD Xaverius 1 Jambi based on parents’ perspective. This research was conducted from January to March. This research is qualitative research. The research subjects were the parents of 25 class VIB students. The research was conducted at SD Xaverius 1. Data collection was obtained through a process of interviews, and documentation. The analysis of the data used is more descriptive and descriptive in nature from the results of interviews and observations of the object of research and the presentation of data through tables and diagrams. This study shows that parents feel a good impact on the development of children's character through learning the CHIPS Model character education in schools. Children show very good small changes such as diligently worshiping, greeting, giving thanks and being grateful. The CHIPS model learning material is also generally accepted, but it is better to make a few updates so that it can be more accepted by many parties and dynamic according to the times. Keywords: education, character, spiritual, CHIPS, parents